2015
DOI: 10.1016/j.oooo.2014.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Frequent inactivation of SLIT2 and ROBO1 signaling in head and neck lesions: clinical and prognostic implications

Abstract: Our data suggest that inactivation of SLIT2 and/or ROBO1 is one of the early events in development of dysplastic lesions of head and neck and has prognostic importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
(36 reference statements)
1
11
0
Order By: Relevance
“…Among these 27 genes enrolled in IRGS, six genes (ULBP1, CCR6, CCL22, ROBO1, DKK1 and PDGFA) have previously shown to correlate with the tumorigenesis of HNSCC [20][21][22][23][24][25]. As reported, CCR6 Fig.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Among these 27 genes enrolled in IRGS, six genes (ULBP1, CCR6, CCL22, ROBO1, DKK1 and PDGFA) have previously shown to correlate with the tumorigenesis of HNSCC [20][21][22][23][24][25]. As reported, CCR6 Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Reliable prognostic biomarkers are needed to identify patients with the highest risk of unfavorable survival outcomes. Numerous studies have highlighted the biomarkers associated with the pathogenesis and biology of HNSCC [14,[20][21][22][23][24][25]. Unfortunately, the accuracy of their survival evaluations remains limited and they have not yet been applied in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced Slit2 expression has been reported in a great variety of cancers, and is predominantly due to the hypermethylation of the Slit2 promoter (34)(35)(36)(37)(38)(39). Although Slit2 downregulation has also been reported in HCC tissues (21), large-scale mining of microarray data from the Oncomine database revealed a heterogeneous expression pattern for Slit2 in HCC clinical samples (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Robo1 and Robo2 are two receptors of the secretory protein Slit2. It was previously reported that Slit2 and Robo1 are expressed in a large number of malignant solid tumors and the binding of the functional region of Slit2 to Robo1 could initiate a cascade of events leading to altered cell proliferation, migration, apoptosis, and angiogenesis [12,23,24]. Up-regulation of Robo1 has been reported to be correlated with poor prognosis of nasopharyngeal cancer (NPC) [20,23].…”
Section: Discussionmentioning
confidence: 99%